Answer: x = 3 √21
Step-by-step explanation:
you gotta use our good, old, trusty friend pythagorean theorem.
a^2 + b^2 = c^2
x^2 + 6^2 = 15^2
x^2 = 15^2 - 6^2
x^2 = 189
x = √189
x = √27 · 7
x = 3 √3 · 7
x = 3 √21
Answer:
3
1
if your estimating to whole numbers the 3 1/8 is 3 and 1 2/5 is 1
Step-by-step explanation:
They give us 2 pieces to the puzzle. Both are positive numbers...x and y.
1.) 1 number is 1 less than twice another number. (x = 2y -1)...and
2.) the sum of their squares is 106. (x^2 + y^2 = 106).
substitute the value for x into the second equation.
(2y-1)^2 + y^2 = 106
(2y-1) (2y-1) + y^2 = 106 (use distributive property)
4y^2 - 2y - 2y + 1 + y^2 = 106 (subtract 106 from both sides)
4y^2 - 2y - 2y + 1 + y^2 - 106 = 106 - 106 (combine like terms)
5y^2 - 4y - 105 = 0 (factor)
(y-5) (5y-21) = 0 (set to 0)
y - 5 = 0
y = 5
substitute the 5 into the equation for y (x = 2(5) - 1)
x = 9 if we square 9, we get 81.
subtracted from 106 we have 25...the square root of 25 is 5.
our answers are 5 and 9.
Answer:
11 and 11
Step-by-step explanation:
brainliest^:)